Structural and phenomenological characterization of the thermoreversible sol-gel transition of a zirconyl aqueous precursor modified by sulfuric acid - Chiavacci, L. A.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, V (Amer Chemical Soc, 1998)
The thermoreversible sol-gel transition is well-known in biological and organic polymeric systems but has not been reported for inorganic systems. In this paper we put in evidence a thermoreversible sol-gel transition for zirconyl chloride aqueous solutions modified by sulfuric acid in the ratio 3:1 Zr:SO4. The synthesis conditions are detailed and a variety of experimental techniques (turbidimetry, dynamic rheology, and EXAFS) have been employed for investigating the thermal reversibility and the chemical structure of this new material. Turbidimetric measurements performed for solutions containing different concentrations of precursor have evidenced that the sol-gel transformation temperature increases from 50 to 80 degrees C as the concentration of zirconyl chloride decreases from 0.22 to 0.018 mol L-1. A more detailed study has been done for the sample with [Zr] = 0.156 mol L-1, in which the sol-gel-sol transformation has been repeated several times by a cyclic variation of the temperature. The mechanical properties of this sample, evaluated by measuring the storage and the loss moduli, show a change from liquid like to viscoelastic to elastic behavior during the sol-gel transition and vice versa during the gel-sol one. In situ EXAFS measurements performed at the Zr K-edge show that no change of the local order around Zr occurs during the sol-gel-sol transition, in agreement with the concept of physical gel formation. We have proposed for the structure of the precursor an inner core made of hydroxyl and oxo groups bridging together zirconium atoms surrounded in surface by complexing sulfate ligands, the sulfate groups act as a protective layer, playing a key role in the linking propagation among primary particles during sol-gel-sol transition.